FAKTOR YANG MEMENGARUHI PURCHASE INTENTION KONSUMEN INDONESIA SAAT BELANJA ONLINE - Sheilla Fauzia Rahmi; Kurniawati Kurniawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Purchase intention is an important trigger that motivates shoppers to shop online through smartphones. Therefore, it is essential to identify determinant factors of customers in Indonesia’s purchase intention on online shopping. This research examines internet self-efficacy, perceived aesthetics to purchase intention directly or mediated through perceived benefit. The study of the impact of hedonic motivations of adventure on purchase intention is also analyzed. The paper carried out a non-probability sampling on a purposive sample of 248 shoppers in Indonesia collected via an online survey. The data of this study were tested using PLS-SEM (Partial Least Squares-Structure Equation Modeling) to test hypotheses. The result of this study indicates that hedonic motivations of adventure and perceived benefit positively affect purchase intention. Internet self-efficacy and perceived aesthetics have a positive impact on perceived benefit. This study also shows that internet self-efficacy and perceived aesthetics positively affect purchase intention mediated by a perceived benefit.